Maternal-Fetal HLA Compatibility in Uncomplicated and Preeclamptic Naturally Conceived Pregnancies - van ‘t Hof, Liseanne J.; Schotvanger, Naomi; Haasnoot, Geert W.; van der Keur, Carin; Roelen, Dave L.; Lashley, Lisa E. E. L. O.; Claas, Frans H. J.; Eikmans, Michael; van der Hoorn, Marie-Louise P. (Frontiers in Immunology, 2021)
Introduction: In pregnancy, the mother and fetus differ in HLA antigens, and yet the maternal immune system generally tolerates the fetus. KIR receptors expressed by maternal uterine NK cells at the maternal-fetal interface directly interact with HLA-C on extravillous trophoblast cells for optimal placental development. In this study, we aimed to determine whether there is a preferential selection for HLA compatibility and specific KIR/HLA-C combinations in uncomplicated and preeclamptic naturally conceived pregnancies compared to what would be expected by chance. Methods: Genotyping for maternal and fetal HLA-A, -B, -C, -DR, and -DQ, and maternal KIR was performed for 451 uncomplicated pregnancies and 77 pregnancies complicated with preeclampsia. The number of HLA antigen (mis)matches between mother and fetus was calculated and compared to expected values obtained by randomization of the HLA haplotype, inherited from the father, over the existing maternal haplotype of the fetuses. A similar methodology was executed for analysis of the KIR/HLA-C data (n=309). Results: In uncomplicated pregnancies, the degree of maternal-fetal HLA matching was not different than expected-by-chance values. In preeclamptic pregnancies, the degree of maternal-fetal HLA matching was different in observed compared to expected-by-chance values (p=0.012). More specifically, the degree of maternal-fetal matching of HLA-C was higher in the actual preeclamptic pregnancies than was expected-by-chance (p=0.007). Preeclamptic pregnancies showed an overall tendency towards higher maternal-fetal HLA compatibility, for total HLA matches (p=0.021), HLA class I (p=0.038) and HLA-C (p=0.025) compared to uncomplicated pregnancies. Conclusion: The data suggest that there is no preferential selection of maternal-fetal HLA compatibility in uncomplicated pregnancies. In contrast, increased total HLA, HLA class I and, especially, HLA-C compatibility is associated with preeclampsia, suggestive for a role of HLA mismatches in immune regulation leading to uncomplicated pregnancy.